Sustainability of Biodiversity in Bhutan - Kumar Nepal, Tej (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Biodiversity is the variety of life on Earth. The Eastern Himalaya biodiversity hotspot (EH) is part of 36 biodiversity hotspots of the world. EH is around 7,50,000 km2 covering Bhutan, Nepal, southeast Tibet (China), northern Myanmar, and the Indian territories of Assam, Arunachal Pradesh, West Bengal, and Sikkim. The whole of Bhutan (38,394 km2) falls in the EH biodiversity hotspot. The exclusive biodiversity is heaven for biodiversity as the country’s total forest cover exceeds 70 %. Bhutan’s five National Parks, four Wildlife Sanctuaries, one Strict Nature Reserve, and Biological Corridors are home to some of the globally endangered species like Chinese Pangolin (Manis pentadactyla), Great Hornbill (Buceros bicornis), Red Panda (Ailurus fulgens), Black-necked Crane (Grus nigricollis), White-bellied Heron (Ardea insignis), Bhutan Takin (Budorcas taxicolor whitei) and Bengal Tiger (Panthera tigris tigris). The country is home to around 300 medicinal plants, raw materials for the country’s traditional medicine. The glaciers in the Bhutanese Himalaya are retreating at a fast rate. The management of Protected Areas, using non-wood products, going green, and waste management at the individual level are essential for biodiversity sustainability.